Cryptomarkets : a research companion - Martin, James; Cunliffe, Jack; Munksgaard, Rasmus (Emerald studies in digital crime, technology and social harms, 2019)
Since the launch of the infamous Silk Road, the use of cryptomarkets - illicit markets for drugs on the dark web - has expanded rapidly around the world. Cryptomarkets: A Research Companion is an accessible, detailed guidebook which offers all the tools necessary to begin researching cryptomarket phenomena and the dark web trade in illicit drugs.Offering an in-depth historical account of the development of cryptomarkets up until the present day, the book goes on to examine key trends and findings regarding the contemporary operations of cryptomarkets. The principal methodologies used to conduct cryptomarket research, as well as questions regarding research ethics, are further explored. Finally, the authors outline underdeveloped areas of the field and pose key questions for future cryptomarket research.Whether an academic researcher, post-graduate student, law enforcement officer, or public health professional, this book is essential reading for those researching and working in the realm of cryptomarkets.